2021 Penyuluhan Impementasi Kebijakan Vaksinasi Covid 19 Dalam Mencegah Penyebaran Wabah - Suharti, Sri; Ulsa, Amei Fatimah; Prananda, Ones; Rifai , Muhammad; Ramdhan, Dwiki Akbar (Jurnal Kewirausahaan dan Bisnis, 2021)
Covid-19 vaccination has been the main focus of efforts to prevent the spread of this global pandemic. The implementation of vaccination policies is crucial in responding to the public health challenges caused by this pandemic. This article examines the effectiveness of extension in increasing the level of community participation in the Covid-19 vaccination program. The extension method is used as a means to educate the public about the benefits of vaccination and the importance of actively participating in the vaccination program. The results showed that counseling was effective in increasing community understanding of Covid-19 vaccination. Counseling also succeeded in reducing the reluctance and doubts that often arise among the community towards the Covid-19 vaccine. Factors such as accessibility, trust, and clear information are key in the success of vaccination extension programs. In this context, the role of public health extension workers is crucial in approaching and educating the public about vaccination. This article also highlights the importance of collaboration between the government, health institutions, and community organizations in disseminating information about Covid-19 vaccination. In conclusion, the implementation of effective counseling is an integral component in efforts to prevent the spread of the Covid-19 outbreak through vaccination, by involving various parties in disseminating accurate and relevant information to the public.